Cerebrovascular damage caused by the gut microbe/host co-metabolite p-cresol sulfate is prevented by blockade of the EGF receptor - Sita N. Shah; Tobias B-A. Knausenberger; Matthew G. Pontifex; Emily Connell; Gwénaëlle Le Gall; Tom A.J. Hardy; David W. Randall; Kieran McCafferty; Muhammad M. Yaqoob; Egle Solito; Michael Müller; Andrew V. Stachulski; et al. (Gut Microbes)
The gut microbiota-brain axis has been associated with the pathogenesis of numerous disorders, but the mechanism(s) underlying these links are generally poorly understood. Accumulating evidence indicates the involvement of gut microbe-derived metabolites. Circulating levels of the gut microbe/host co-metabolite p-cresol sulfate (pCS) correlate with cerebrovascular event risk in individuals with chronic kidney disease (CKD), but whether this relationship is mechanistic is unclear. We hypothesized that pCS would impair the function of the blood–brain barrier (BBB), the primary brain vasculature interface. We report that pCS exposure impairs BBB integrity in human cells in vitro and both acutely (≤6 hours) and chronically (28 days) in mice, enhancing tracer extravasation, disrupting barrier-regulating tight junction components and ultimately exerting a suppressive effect upon whole-brain transcriptomic activity. In vitro and in vivo mechanistic studies showed that pCS activated epidermal growth factor receptor (EGFR) signaling, sequentially activating the intracellular signaling proteins annexin A1 and STAT3 to induce mobilization of matrix metalloproteinase MMP-2/9 and disruption to the integrity of the BBB. This effect was confirmed as specific to the EGFR through the use of both pharmacological and RNA interference approaches. Confirming the translational relevance of this work, exposure of the cerebromicrovascular endothelia to serum from hemodialysis patients in vitro led to a significant increase in paracellular permeability, with the magnitude of permeabilization closely correlating with serum pCS, but not most other uremic toxin, content. Notably, this damaging effect of hemodialysis patient serum was prevented by pharmacological blockade of the EGFR. Our results define a pathway linking the co-metabolite pCS with BBB damage and suggest that targeting the EGFR may mitigate against cerebrovascular damage in CKD. This work further provides mechanistic evidence indicating the role of gut microbe-derived metabolites in human disease.